Reflections on social work 2020 under Covid-19 online magazine. Issue 8 (16th November 2020) - Sen, Robin; Featherstone, Brid; Gupta, Anna; Kerr, Christian; MacIntyre, Gillian; Quinn-Aziz, Abyd
ABSTRACT: Social Work 2020 under Covid-19 was a free online magazine conceived just before the UK's Covid-19 full lockdown began, in late March 2020. It ran for five editions until 14 July 2020. In this time it published close to 100 articles from academics, people with lived experience, practitioners and students. It contained a far higher proportion of submissions from the last three groups of contributors than traditional journals. This article draws on the six-person editorial collective's reflections on the magazine: it considers its founding purposes; its role in fostering social work community, utilizing an adaptation of social capital classifications; and its potential as a learning tool. It concludes by arguing that the magazine illustrates the potential for free online publications to be an important emergent vehicle for 'everyday activism' within the field of social work.